2015
DOI: 10.1037/cpb0000027
|View full text |Cite
|
Sign up to set email alerts
|

The wealthy: A financial psychological profile.

Abstract: Drawing from the theories of money ambivalence, cognitive dissonance, envy, and relative deprivation, this study sought to explore stereotypes of the wealthy. Specfically, it examined the financial psychology, demographics, and financial behaviors of a sample of wealthy individuals and a sample of other relatively high-income and high-net-worth individuals, and it compared these characteristics to see what, if any, differences exist. Results show that wealthy individuals exhibited significant psychological dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(78 reference statements)
1
7
1
Order By: Relevance
“…From those struggling to make ends meet to the wealthy, money can have a profound effect on psychological wellbeing (Klontz, Sullivan, Seay, & Canale, 2015;Mani, Mullainathan, Shafir, & Zhao, 2013). When financial stress adversely impacts financial and psychological health, it is important to rule-out the presence of a money disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From those struggling to make ends meet to the wealthy, money can have a profound effect on psychological wellbeing (Klontz, Sullivan, Seay, & Canale, 2015;Mani, Mullainathan, Shafir, & Zhao, 2013). When financial stress adversely impacts financial and psychological health, it is important to rule-out the presence of a money disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement motivation, in turn, is associated with both better grades in the classroom (Fortier, Vallerand, & Guay, 1995) and higher job satisfaction in the workplace (Wang, Bowling, & Eschleman, 2010). Furthermore, internal LOC has been found to be associated with higher income and wealth (Klontz, Seay, Sullivan, & Canale, 2014;Klontz, Sullivan, Seay, & Canale, 2015;Zagorsky, 2007). In contrast, people with external LOC tend to attribute their actions to fate, luck, or other people (Schultz & Schultz, 2013).…”
Section: Locus Of Control (Loc)mentioning
confidence: 99%
“…Items were removed from the KMSI that had factor loadings of less than .40 and that did not significantly contribute to the subscales' Cronbach's alpha. The KMSI-R has demonstrated strong reliability in several large-sample studies (Britt et al, 2015;Klontz et al, 2014;Klontz et al, 2015). The KMSI-R consists of the same four subscales as the KMSI (i.e., Money Avoidance, Money Worship, Money Status, and Money Vigilance) and the KMSI-R consists entirely of select items from the original measure.…”
Section: General Structure Of the Kmsi-rmentioning
confidence: 99%
“…Beliefs about money have been found to relate to self-esteem and self-worth (Hira & Mugenda, 1999) and money is strongly associated with happiness in many cultures worldwide (Diener & Oishi, 2000). A growing body of research has found that beliefs about money are associated with income, net worth, financial health, choice of profession, and a range of healthy and disordered financial behaviors (Britt, Klontz, Tibbetts, & Leitz, 2015;Klontz, Britt, Mentzer, & Klontz, 2011;Klontz, Seay, Sullivan, & Canale, 2014;Klontz, Sullivan, Seay, & Canale, 2015). While the impact of ISSN: 1945-7774 CC by 3.0 2016 Financial Therapy Association 2 financial beliefs on behaviors and financial outcomes cannot be overstated, relatively few empirically-based scales exist to assess money beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation